Case Billerud and the Proportionality of the EU ETS Excess Emissions Penalty - Peuraniemi, Laura (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis focuses on the proportionality of the excess emissions penalty of the EU emissions trading scheme (ETS). The operators covered by the ETS have an annual obligation to surrender a sufficient number of allowances to cover their emissions of the previous year on a given time, under penalty of an excess emissions penalty. In the case Billerud, the ECJ concluded that this lump sum penalty cannot be adjusted on ground of the principle of proportionality. The ruling gives reason for challenge since it leaves no room for consideration of individual circumstances that could genuinely ensure the proportionate nature of the fine, in particular, where a company has actually had enough allowances in its holding and the failure to surrender them is reasonably justified. At the centre of this thesis lie the case Billerud and the problematics therein. It is examined what kind of drawbacks fixed penalties might have, how the ECJ justified its Billerud ruling and whether that reasoning is convincing. In addition, it is assessed whether the ECJ could have ruled the case differently. The research is executed by interpreting EU legislation, legal literature and the ECJ´s case law. The enforcement of EU competition law penalties is chosen as a point of comparison. It is noted that fixed penalties can be of practical use in certain limited situations where the harm is difficult to assess and the amount of fines remains rather low. Neither of these conditions was met in Billerud. The judgment is not problematic only form the viewpoint of the principle of proportionality, but also with respect to the equality principle. Indeed, due to the fixed penalty, every case where an operator has not returned the allowances on time are handled in the same way, without considering whether these cases similarly affect the scheme´s objective of environmental protection. It is concluded that the ECJ could have come to a less restrictive conclusion proportionate-wise, yet the legal praxis is unlikely to be changed as the Billerud ruling was confirmed in the case Bitter.